Corrigendum to: A Study on IIIA Group Metals (B or Ga or Tl) Doped Mo2C-HZSM-5 Catalysts for Methane Dehydroaromatization - Pasupulety, Nagaraju (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
CORRIGENDUM TO:Pasupulety, N., Alamoudi, M. A., Al-Zahrani, A. A. (2025). A Study on IIIA Group Metals (B or Ga or Tl) Doped Mo2C-HZSM-5 Catalysts for Methane Dehydroaromatization. Bulletin of Chemical Reaction Engineering & Catalysis, 20(4), 631-639. DOI: https://doi.org/10.9767/bcrec.20477This article has been corrected by Authors as follow:Corrections to References cited were done by Authors for improving validity, i.e. [12], [19-20], [22-23], [25-31], [33], [35-38], to the article DOI: 10.9767/bcrec.20477.Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).